Murine Aortic Smooth Muscle Cells Acquire, Though Fail to Present Exogenous Protein Antigens on Major Histocompatibility Complex Class II Molecules. (20th July 2014) - Maddaluno, Marcella; MacRitchie, Neil; Grassia, Gianluca; Ialenti, Armando; Butcher, John P.; Garside, Paul; Brewer, James M.; Maffia, Pasquale
Abstract : In the present study aortic murine smooth muscle cell (SMC) antigen presentation capacity was evaluated using the E α -GFP/Y-Ae system to visualize antigen uptake through a GFP tag and tracking of E α peptide/MHCII presentation using the Y-Ae Ab. Stimulation with IFN- γ (100 ng/mL) for 72 h caused a significant ( P < 0.01 ) increase in the percentage of MHC class II positive SMCs, compared with unstimulated cells. Treatment with E α -GFP (100 μ g/mL) for 48 h induced a significant ( P < 0.05 ) increase in the percentage of GFP positive SMCs while it did not affect the percentage of Y-Ae positive cells, being indicative of antigen uptake without its presentation in the context of MHC class II. After IFN- γ -stimulation, ovalbumin- (OVA, 1 mg/mL) or OVA323–339 peptide-(0.5 μ g/mL) treated SMCs failed to induce OT-II CD4 + T cell activation/proliferation; this was also accompanied by a lack of expression of key costimulatory molecules (OX40L, CD40, CD70, and CD86) on SMCs. Finally, OVA-treated SMCs failed to induce DO11.10-GFP hybridoma activation, a process independent of costimulation. Our results demonstrate that while murine primary aortic SMCs express MHC class II and can acquire exogenous antigens, they fail to activate T cells through a failure in antigen presentation and a lack of costimulatory molecule expression.